From Body Structure to Bodies in Resonance: Evolution of the Therapeutic Relationship in Bioenergetic Analysis - Pla, Fina (Bioenergetic Analysis, 2017)
This article takes the reader on a journey with two different parts. In the first one, contributions on the transference/countertransference theme provided by bioenergetic authors are presented giving an overview of the richness and creativity of each author. In the second part, a reflection about the impact of Attachment Theory, Relational Psychoanalysis and Neuroscience in the therapeutic relationship in Bioenergetic Analysis is provided. The impact of new concepts is exposed and the rethinking of old ones is revised. The result is a new, enriched view of the therapeutic relationship and its transferential/countertransferential processes where the therapeutic process becomes an interrelational somatosensory process within the therapeutic dyad. Some short clinical vignettes are provided.